Effects of Cutting Length and Position on the Seed Yield and Quality of Tossa Jute (Corchorus olitorius L.) (The Agriculturists, 2018)
An experiment was conducted at the research field of Jute Research Regional Station of Bangladesh Jute Research Institute (BJRI) at Kishoreganj during August 2009 to January 2010 to assess the effect of cutting length and position of cutting on seed yield and quality of tossa jute (Corchorus olitorius L.). Three cutting lengths (15 cm, 20 cm and 25cm) and three cutting positions (1st top, 2nd top and 3rd top) were the treatments. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The highest seed yield (917 kg ha-1) was obtained from 1st top x 15cm interaction and the lowest (811 kg ha-1) was recorded in 3rd top x 25cm cutting length. The highest seed germination (89%), field emergence (87%) and accelerated ageing (73%) were recorded from 1st top x 15cm interaction and the lowest seed germination (83.00%), field emergence (81%) and accelerated ageing (72) were recorded in 3rd top x 25 cm cutting length. The upper position of cutting produced the highest yield and best quality seeds. The Agriculturists 2018; 16(1) 13-20